Pengaruh Kompetensi SDM dan Sistem Informasi Akuntansi terhadap Kinerja Keuangan Organisasi - Basri; Saddiya Hamris; Martang Martang; Aprisda Kemala Bhayangkari (Movere Journal, 2026)
The This study aims to analyze the influence of human resource (HR) competencies on organizational financial performance both directly and indirectly through the Accounting Information System (SIA) at the Gowa Regency DPRD Secretariat Office. This study uses a quantitative approach with a survey method. Data was collected through the distribution of questionnaires to 45 respondents who are apparatus involved in the organization's financial management. Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of SmartPLS 3 software. The results of the study show that human resource competence has a positive and significant effect on the financial performance of the organization. In addition, human resource competence also has a positive and significant effect on the Accounting Information System. Furthermore, the Accounting Information System has been proven to have a positive and significant effect on the financial performance of the organization. The results of the indirect influence test show that the Accounting Information System is able to mediate the influence of human resource competencies on the organization's financial performance. These findings indicate that improving the competence of the apparatus, especially in terms of knowledge, skills, and work attitudes, is very important in supporting the implementation of an effective Accounting Information System to improve the financial performance of the organization. This research provides practical implications for managers of public sector organizations to focus policies on developing human resource competencies and strengthening accounting information systems in an integrated manner to realize transparent and accountable financial management